Analysis of Work Stress Among Bank Employees: A Case Study of Bank Rakyat - Aliah, Roslan (2011)
The purpose of this study is to determine factors of work stress among the Bank Rakyat’s employees. This study also aims to determine whether there were any statistically significant differences in the respondents’ level of work stress by demographic factors (gender, status, education qualification, job position and length of service). The survey was carried out at 12 branches of Bank Rakyat at Northern Zone. A total of 154 bank employees participated in this study. Data was collected through 40 items questionnaires on a five-point Likert Scale. Both descriptive and inferential statistics were used to analyze the data using the SPSS version 15.0. Correlation analyses were conducted to test the relationship between levels of work stress with personal factors, organizational factors and environmental factors; whereas descriptive analysis was conducted to analyze demographic characteristics of respondents. Besides that, T-test, ANOVA and regression were also used in this study. The findings of this study showed that there was no statistically significant difference in the level of work stress by demographic factors (gender, status, education qualification, job position and length of service). However, the findings showed that only organizational factors have significant relationship with work stress level. Findings of this study also resulted in the overall level of work stress among respondent is moderate.